2018
DOI: 10.17784/mtprehabjournal.2018.16.594
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the autonomic system, pulmonary function and sleep disorders in hypertensive patients submitted to aerobic training. A study protocol

Abstract: Background: Systemic arterial hypertension (SAH) is a common cardiovascular disease that reflects an important incidence and prevalence for public health, with obstructive sleep apnea (OSA) being considered the second cause of SAH. Aerobic exercise is one of the actions to control blood pressure changes. Objectives: To verify the anthropometric profile, the physical fitness, the pulmonary function, the presence of respiratory sleep disorders and the behavior of the autonomic activity in hypertensive patients s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…So, it is necessary to discuss the variables that could contribute for reduction of the problems associated with sleep, including the non-pharmacological methods, where it is possible to include the regular practice of physical exercise (27) Besides that, showed that inadequate levels of sleep duration are associated with increase of overweight and obesity in adolescents (28) .…”
Section: Discussionmentioning
confidence: 99%
“…So, it is necessary to discuss the variables that could contribute for reduction of the problems associated with sleep, including the non-pharmacological methods, where it is possible to include the regular practice of physical exercise (27) Besides that, showed that inadequate levels of sleep duration are associated with increase of overweight and obesity in adolescents (28) .…”
Section: Discussionmentioning
confidence: 99%